Menggabungkan Pelaksanaan Dua Ibadah Sejenis dalam Pelaksanaannya Menurut Kaidah Fiqh - Taqwim, Andi Ahsan; Musyahid, Achmad; Akmal, Andi Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This paper discusses the rules of jurisprudence regarding the combination of two similar acts of worship in one implementation with one intention. In the practice of worship, a Muslim is often faced with a condition where two acts of worship that have the same type and purpose occur at the same time. Based on the rules of jurisprudence: “If two similar acts of worship come together then their implementation is combined and it is sufficient to carry out one of them if both have the same purpose”, then this combination is permitted with certain conditions. This research uses a qualitative method based on literature study by reviewing relevant literature regarding the rules of jurisprudence and their application. The results of the discussion show that combining two similar worship services is permissible if it meets conditions such as: the type of worship is the same, the time is the same, it is not a qadha or accompanying worship service, and the intention of a larger worship service if there is a difference in degree. Examples of implementation include: janabah bathing at the same time as Friday bathing, tawaf ifadhah and tawaf wada’, as well as sunnah ablution, qabliyah and tahiyyatul mosque prayers simultaneously. In conclusion, this rule shows the ease in Islamic law while maintaining the validity and value of worship.